2019
DOI: 10.1088/2058-8585/ab56dd
|View full text |Cite
|
Sign up to set email alerts
|

Organic photodiodes: printing, coating, benchmarks, and applications

Abstract: Organic photodiodes (OPDs) are set to enhance traditional optical detection technologies and open new fields of applications, through the addition of functionalities such as wavelength tunability, mechanical flexibility, light-weight or transparency. This, in combination with printing and coating technology will contribute to the development of cost-effective production methods for optical detection systems. In this review, we compile the current progress in the development of OPDs fabricated with the help of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(85 citation statements)
references
References 98 publications
2
83
0
Order By: Relevance
“…Very recently, this energetic tunability allowed record efficiencies of 26% for indoor light harvesting to be reached 11. Additionally, their processability via printing techniques enables high‐throughput additive manufacturing on thin and mechanically flexible substrates with full freedom of design 12–15. Previous studies have shown that printed OPDs can compete with commercial photodiodes based on inorganic materials in terms of responsivity, dark current and linear dynamic range 16–21.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…Very recently, this energetic tunability allowed record efficiencies of 26% for indoor light harvesting to be reached 11. Additionally, their processability via printing techniques enables high‐throughput additive manufacturing on thin and mechanically flexible substrates with full freedom of design 12–15. Previous studies have shown that printed OPDs can compete with commercial photodiodes based on inorganic materials in terms of responsivity, dark current and linear dynamic range 16–21.…”
Section: Figurementioning
confidence: 99%
“…Previous studies have shown that printed OPDs can compete with commercial photodiodes based on inorganic materials in terms of responsivity, dark current and linear dynamic range 16–21. However, in their great majority, these OPDs utilize active layers developed for photovoltaic applications and are therefore designed to have a broad absorption range which aims to match the solar spectrum 14. As such, these devices have relied on device engineering approaches to limit their spectral responsivity range.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…4,6 . These can be broadly classified into light-based methods such as photolithography 16 and laser-induced forward transfer (LIFT) 17,18 ; printing methods such as inkjet, vapour jet and aerosol jet [19][20][21][22][23] , and contact methods such as hard and soft imprint lithography [24][25][26] . Of these, photolithography represents the most mature technology, with a further advantage being its high spatial resolution (~1 μm in large-field proximity-mode implementations).…”
mentioning
confidence: 99%